Cold Exposure Induces Depot-Specific Alterations in Fatty Acid Composition and Transcriptional Profile in Adipose Tissues of Pigs - Zhou, Yanbing; Xu, Ziye; Wang, Liyi; Ling, Defeng; Nong, Qiuyun; Xie, Jintang; Zhu, Xiaodong; Shan, Tizhong (Frontiers in Endocrinology, 2022)
Cold exposure promotes fat oxidation and modulates the energy metabolism in adipose tissue through multiple mechanisms. However, it is still unclear about heat-generating capacity and lipid mobilization of different fat depots without functional mitochondrial uncoupling protein 1 (UCP1). In this study, we kept finishing pigs (lack a functional UCP1 gene) under cold (5-7 ℃) or room temperature (22-25 ℃) and determined the effects of overnight cold exposure on fatty acid composition and transcriptional profiles of subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). And the plasm metabolomes of porcine was also studied by LC-MS-based untargeted metabolomics. We found that the saturated fatty acids (SFAs) content was significantly decreased in SAT upon cold exposure. While in VAT, the relative content of lauric acid (C12:0), myristic acid (C14:0) and lignoceric acid (C24:0) were dramatically decreased without affecting total SFA content. RNA-seq results showed SAT possess active organic acid metabolism and energy mobilization upon cold exposure. Compared with SAT, cold-induced transcriptional changes were far less broad in VAT, and the differentially expressed genes (DEGs) were mainly enriched in fat cell differentiation and cell proliferation. Moreover, two plasm metabolomes, taurine and creatin, were enhanced in plasm upon overnight cold treatment, suggesting cold exposure induced lipid and fatty acid metabolism in white adipose tissue (WAT) might be regulated by functions of taurine and creatine. These results provide new insights into the effects of short-term cold exposure on lipid metabolism in adipose tissues without functional UCP1.